Pengaruh Lingkungan Sekolah dan Pemanfaatan Perpustakaan terhadap Hasil Belajar Siswa dengan Motivasi Belajar Sebagai Variabel Intervening - Armiati, Armiati; Oktavia, Yola; Hidayat, M Topit (Jurnal Ecogen, 2024)
This research aims to analyze the influence of the school environment and library use on student learning outcomes through learning motivation as an intervening variable. This type of research is quantitative with an associative type. The research population was class The sampling technique was proportional random sampling with a sample size of 168 students. The data used are primary and secondary data. The data collection technique is in the form of a questionnaire. Data analysis uses descriptive analysis, analysis prerequisite tests, path analysis, t test and coefficient of determination. Data analysis using SPSS. The research results show that 1) the school environment has a direct effect on learning outcomes 2) library use has no direct effect on learning outcomes 3) the school environment has no effect on learning outcomes through learning motivation as an intervening variable 4) library use has an effect on student learning outcomes through motivation learning as an intervening variable.